2006
DOI: 10.1111/j.2006.0030-1299.14143.x
|View full text |Cite
|
Sign up to set email alerts
|

A mutualism's indirect costs: the most aggressive plant bodyguards also deter pollinators

Abstract: Ness, J. H. 2006. A mutualism's indirect costs: the most aggressive plant bodyguards also deter pollinators. Á Oikos 113: 506 Á514.Plant defenses against herbivores may be costly if they exclude mutualists. Here, I test the hypothesis that aggressive ant bodyguards of plants deter pollinators, and explore mechanisms by which Ferocactus wislizeni , an extrafloral nectary bearing cactus, limits conflicts between its pollinators and bodyguards. Flower visitation by ants and pollinating bees differed among plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
197
2
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(217 citation statements)
references
References 48 publications
8
197
2
10
Order By: Relevance
“…However, ants can also impose ecological costs on plants if they negatively affect the interactions between their host plants and other organisms in the environment. For example, ants can deter pollinators (Ness 2006) or increase herbivore loads on their host plants (Frederickson and Gordon 2007;Palmer et al 2008), such as by tending scale insects or aphids (Styrsky and Eubanks 2007). Direct and ecological costs are tightly linked (e.g., investing in ants instead of growth may reduce a plant's competitive ability; see also Heil 2002), but nonetheless we think the distinction is useful because of the different implications of direct and ecological costs for the evolution of cheating.…”
Section: Introductionmentioning
confidence: 99%
“…However, ants can also impose ecological costs on plants if they negatively affect the interactions between their host plants and other organisms in the environment. For example, ants can deter pollinators (Ness 2006) or increase herbivore loads on their host plants (Frederickson and Gordon 2007;Palmer et al 2008), such as by tending scale insects or aphids (Styrsky and Eubanks 2007). Direct and ecological costs are tightly linked (e.g., investing in ants instead of growth may reduce a plant's competitive ability; see also Heil 2002), but nonetheless we think the distinction is useful because of the different implications of direct and ecological costs for the evolution of cheating.…”
Section: Introductionmentioning
confidence: 99%
“…5 But, indirect effects have been studied most extensively in the context of trophic cascades when top predators are removed 6 or added 7 and in the context of mutualisms. [8][9][10] Usually, indirect effects are investigated as changes in abundance of the focal species occur. However, indirect effects may result in biologically significant changes in a species that are not reflected only to its abundance.…”
mentioning
confidence: 99%
“…Flower visits by this insect were significantly more frequent, and their duration significantly longer, on plants with ants present. This result was surprising, as aggressive ants have more often been seen to deter pollinators (Ness 2006;Assunção et al 2014;Ohm and Miller 2014), and pollinators have been observed to recognize the danger posed by ants (Hernández-Cumplido et al 2010;Assunção et al 2014). We are not alone, however, in observing increased pollination rates in the presence of ants.…”
Section: Discussionmentioning
confidence: 87%
“…These plants, however, receive fewer and shorter visits from pollinators, which are deterred by the same ferocious ants (Ness 2006). Understanding the outcome of ant-plant interactions, therefore, requires that we focus on the broad multi-guild, multi-trophic interactions of which they are a part.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation